2019
DOI: 10.1124/dmd.118.086074
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Carboxylesterase 1 by Major Cannabinoids and Selected Metabolites

Abstract: The escalating use of medical cannabis and significant recreational use of cannabis in recent years has led to a higher potential for metabolic interactions between cannabis or one or more of its components and concurrently used medications. Although there have been a significant number of in vitro and in vivo assessments of the effects of cannabis on cytochrome P450 and UDP-glucuronosyltransferase enzyme systems, there is limited information regarding the effects of cannabis on the major hepatic esterase, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…The reduced heme converting capacity in the presence of CBs might be the consequence of direct interaction with the enzyme in analogy to the (previously described) inhibition of cytochrome P450 isoenzymes in-vitro by CBD [67][68][69]. We, therefore, checked whether CBs are able to interfere with the HO reaction in-vitro directly.…”
Section: Modulation Of Ho Activity By Cbsmentioning
confidence: 90%
“…The reduced heme converting capacity in the presence of CBs might be the consequence of direct interaction with the enzyme in analogy to the (previously described) inhibition of cytochrome P450 isoenzymes in-vitro by CBD [67][68][69]. We, therefore, checked whether CBs are able to interfere with the HO reaction in-vitro directly.…”
Section: Modulation Of Ho Activity By Cbsmentioning
confidence: 90%
“…An in vitro study with CES1-transfected cells suggested that cannabis [i.e., tetrahydrocannabinol (THC), cannabidiol (CBD), and cannabinol (CBN)] can act as a potential CES1 inhibitor. The inhibition constant (Ki) values for THC, CBD, and CBN were 0.541, 0.974, and 0.263 mM (0.170, 0.306, and 0.0817 mg/ml), respectively (Qian et al, 2019). This result could be clinically impactful because the use of cannabis is expected to increase in the next few years (Hasin, 2018).…”
Section: Drug-drug Interactionsmentioning
confidence: 95%
“…THC has been shown to have broad inhibitory effects on CYP450 enzymes including CYP3A, CYP2D6, CYP2C9, CYP2C19, CYP2A6, CYP2B6, CYP1A1/2, and CYP2J2 [39]. In addition, new evidence suggests that cannabinoids, including THC, have strong inhibitory effects on carboxylesterase 1 (CES1), which is important in the metabolism of many medications [39][40][41]. Overall, THC is less implicated in DDIs compared to CBD, but is still likely to contribute to this risk at clinically relevant concentrations.…”
Section: Thc+cbd Mucosal Spray (Sativex) 4 Spraysmentioning
confidence: 99%